IDENTIFIKASI PENGAWET DAN PEWARNA BERBAHAYA PADA BUMBU GILING - Bagya Mujianto; Angki Purwanti; Siti Rismini (Jurnal Ilmu dan Teknologi Kesehatan, 2013)
The research aims at investigating on the presence of formalin, boraks and hazardous colours (rhodamin B and methanyl yellow) in varios blended cooking spices. The population on this reserch are all banded cooking spices sellers. The amount of samples are 234 items and were analyzed in food labolatory, Health of Politechnic Jakarta III. Form those 234 item samples consisting of 12 kinds of cooking spices found that 1 out of 36 blended chili (2.7%) consist borat, 84 out of 112 blended cooking spices (76.5%) consist formalin, and 4 out of 36 blended chili (11.1%) consist rhodamin B. No methanyl yellow was found in the samples. Guidance and inspection should be improved, especially for the sellers in Pondok Gede and Bantar Gebang market. People are suggested to avoid using blended cooking spices sold in the market.